Young consumers' perception of food quality: an illustration from Greece - Kamenidou I.; Priporas C.-V.; Michailidis A.; Mamalis S. (The market for organic products in the Mediterranean region, 2003)
Food quality is becoming an increasing important factor in consumer's buying decision making, especially after serious safety issues appeared recently in the European Union. The need of standards to assure food quality and safety is evident from literature. The present study explores young consumers' perceptions of food quality. It presents the outcome of a field research undertaken from October 2002 to January 2003. A convenience sample of 582 higher education students aged between 18-23, living away from their homes, in Greece, was employed. Statistical analysis included frequencies, percentages, means, factor analysis, reliability and cluster analysis. The findings from this study are discussed, which are considered to be relevant to marketing practitioners and policy makers for designing appropriate marketing strategies in order to attract and satisfy these segments of young consumers. Lastly, suggestions for further research are presented.
Intensive Course in: Marketing of Organic Products, 2002/05/20-31, Izmir (Turkey)